2018
DOI: 10.1038/s41598-018-27824-0
|View full text |Cite
|
Sign up to set email alerts
|

Rare structural variants in the DOCK8 gene identified in a cohort of 439 patients with neurodevelopmental disorders

Abstract: Detection of copy number variations (CNVs) is a first-tier clinical diagnostic test for children with neurodevelopmental disorders (NDD), which reveals the genetic cause of the disorder in more than 20%. These are mostly known microdeletion/microduplication syndromes, but variants of unknown clinical significance (VOUS) and ambiguous CNVs can also be detected. An example of the last two are abnormalities in the DOCK8 gene. Conflicting interpretations of CNVs affecting DOCK8 can be found in the literature. Dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Also, we identified two sets of host genes, one previously associated with memory, cognition or other neurodevelopmental processes and the other set identified here as candidates for roles in cognition (Table S4). Examples of known human genes associated with memory also identified in our study include: NTM and KLHl20 that are associated with Alzheimer's disease and DOCK8 and KANK1 that are associated with neurodevelopmental disorders including memory potential [29][30][31]. Examples of known mouse genes associated with memory include Specc1 that was identified in a mouse genetic screen for avoidance learning [32], Prdx6 that was associated with neurogenesis and Alzheimer's disease in mice [33,34] and knock-out mice for Abl2, Nrg3, Shank2, Gria1, and Fgf14 that caused neurodevelopmental defects [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 72%
“…Also, we identified two sets of host genes, one previously associated with memory, cognition or other neurodevelopmental processes and the other set identified here as candidates for roles in cognition (Table S4). Examples of known human genes associated with memory also identified in our study include: NTM and KLHl20 that are associated with Alzheimer's disease and DOCK8 and KANK1 that are associated with neurodevelopmental disorders including memory potential [29][30][31]. Examples of known mouse genes associated with memory include Specc1 that was identified in a mouse genetic screen for avoidance learning [32], Prdx6 that was associated with neurogenesis and Alzheimer's disease in mice [33,34] and knock-out mice for Abl2, Nrg3, Shank2, Gria1, and Fgf14 that caused neurodevelopmental defects [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 72%
“…According to a specific woman’s consent to having CNV be reported, we did not communicate these results except for a de novo deletion in the chromosomal band 9p24.3 overlapping the OMIM gene DOCK8 . Recent reports describe, in carriers of DOCK8 deletions, variable clinical manifestations such as intellectual disability, developmental delay, facial dysmorphic features, autism spectrum disorders, and psychiatric behavior [17]. Additionally, duplications encompassing the DOCK8 gene are associated with anomalies in psychiatric behavior [18].…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous loss of function of the DOCK8 gene causes autosomal recessive hyper-IgE recurrent infection syndrome (Zhang et al, 2009). In addition, evidence was recently presented supporting a causal relationship between heterozygous disruption of DOCK8 and mental retardation, pervasive developmental disorders, autism, and bipolar disorders (Nava et al, 2013; Wang et al, 2016; Griggs et al, 2008; Glessner et al, 2017; Krgovic et al, 2018). Our results support the findings of Glessner et al (2017), who identified DOCK8/KANK1 as novel significant loci for ASD and ADHD.…”
Section: Discussionmentioning
confidence: 99%